Transthoracic echocardiography as bedside technique to verify tip location of central venous catheters in patients with atrial arrhythmia. Issue 6 (November 2020) - Iacobone, Emanuele; Elisei, Daniele; Gattari, Diego; Carbone, Luigi; Capozzoli, Giuseppe
Introduction: Transthoracic echocardiography with bubble test is an accurate, reproducible, and safe technique to verify the location of the tip of the central venous catheter. The aim of this study is to confirm the effectiveness of this method for tip location in patients with atrial arrhythmia. Methods: Transthoracic echocardiography with bubble test was adopted as a method of tip location in patients with atrial arrhythmia requiring central venous catheter. If bubbles were evident in the right atrium in less than 2 s after simple saline injection, tip placement was assumed as correct. In cases of uncertain visualization of the bubble effect, the test was repeated injecting a saline–air mixture. Tip location was also assessed by post-procedural chest X-ray. Results: In 42 patients with no evident P-wave at the electrocardiography, we placed 34 centrally inserted central catheters and 8 peripherally inserted central catheters. Transthoracic echocardiography with bubble test detected two centrally inserted central catheter malpositions. In four patients with peripherally inserted central catheter, transthoracic echocardiography with bubble test was positive only when repeated with the saline–air mixture. When the transthoracic echocardiography was positive, the mean (±standard deviation) time for onset of the bubble effect was 0.89 ± 0.33 s in patients with centrally inserted central catheter and 1.1 ± 0.20 s in those with peripherally inserted central catheter; such time difference was not statistically significant (p > 0.05). Conclusion: Tip location of central venous catheter by transthoracic echocardiography with bubble test is feasible, safe, and accurate in patients with atrial arrhythmia. This method can also be applied in peripherally inserted central catheters; however, further studies may be needed to confirm its use in this type of catheters.